The Role of Modern Tax Administration on Tax Services Quality - Ridwan, Risvina; Modding, Basri; Tenriwaru, Tenriwaru (International Journal of Business, Law, and Education, 2024)
This study aims to examine the effect of Modernization of Tax Administration on the Quality of Tax Services at the South Makassar Primary Tax Service Office. The data in this study were obtained from taxpayers registered at KPP Pratama Makassar Selatan in 2022, namely individual taxpayers and corporate taxpayers who were willing to become respondents. This study uses primary data by conducting direct research in the field by giving a questionnaire / statement sheet to respondents and withdrawing samples using the sIovin formula with a total of 100 taxpayer respondents. The analysis that will be used is analysis with multiple regression. The data analysis technique is done by descriptive statistical analysis and SPSS 26.0. The results showed that tax socialization had a positive and significant effect on the quality of tax services, business processes and information technology had a positive and significant effect on the quality of tax services, the implementation of good governance had a positive and significant effect on the quality of tax services and the self-assessment system had a positive and significant effect on the quality of tax services